Symposium 11: Learners' experiences of blended learning environments in a practice context - Thorpe, Mary; Conole, Gráinne; Edmunds, Rob (Proceedings of the International Conference on Networked Learning, 2008)
This project focuses on students studying courses with a work-based learning element. Such courses may require students to do a number of days of practice learning as a compulsory and assessed part of the course. Others develop practical skills as the content of the course or focus on the work practice experience of students. Seven courses have been identified, drawn from Health and Social Care, Mathematics, Computing and Technology, and the Business School. The project focuses on the key research aims of the JISC elearning programme, and constitutes a distinctive context in adding the work and practice dimension to what is to be explored. Issues of skills development and reflecting on practice are central to these courses. Students are also studying part-time and many are older than 25. The project aims: to investigate: the student experience in terms of learners' choices, the critical moments in their evolving practice, and their personalisation of tools and systems; the impact of institutional policies and systems the impact of course-level pedagogic practices and learning outcomes the experience of highly skilled communicators and networkers. A case study on each of the seven courses involved is in the process of development, prior to data collection from students. Interviews with course designers and tutors are being used to surface key issues, some of which can be taken forward into the interviews with students. Issues of student orientation and the design of courses incorporating significant ICT elements are already generating interesting and inter-related issues at this stage in the research process. Students' orientation to technology differs and this creates different kinds of challenge for course providers. For example, students recruited to courses in Health and Social Care include many who are not enthusiastic technology users. Finding themselves studying a course where ICT exercises are assessed and compulsory is described as a'culture shock' by tutors. By contrast, students on a second level Technology course are described as self-selecting and computer literate. ICT integration into course teaching however has required new kinds of design solutions to be devised. A Business School post-graduate course teaches the required ICT skills in an initial tutorial and subsequently summarises this in a wiki. Health and Social Care'front loads' ICT into the first of three courses in the Social Work degree and integrates assessment of key activities into the mandatory assignments and end of course assessed component. The blended aspect of some courses also creates a particular challenge in designing online forums. These can be heavily used in a course where students have to collaborate to generate wiki pages. In a more traditional course context, where the forums are meant for a discursive, group seminar approach, participation has been of good quality from a core in the tutor group, but others have taken part in a more perfunctory fashion - doing just what is stipulated and engaging no further. This project is using a combination of qualitative and quantitative research. Interviews (face to face and telephone) will be analysed using nVIVO. Survey data will use well-established OU processes for online delivery and analysis. These will give us a framework setting a benchmark for how a representative sample of students on the courses use ICT for study, against which we can compare and contrast our qualitative data about particular students. We are also working with a number of Centres of Excellence in Teaching and Learning with shared interests in practice learning. These early findings will be expanded upon at the symposium, with a wealth of new data from the intervening months' work.